Fluorescence signal-to-noise optimisation for real-time PCR using universal reporter oligonucleotides. Issue 28 (26th June 2018) - Lehnert, Michael; Kipf, Elena; Schlenker, Franziska; Borst, Nadine; Zengerle, Roland; von Stetten, Felix
Abstract : In this study we optimised the fluorescence signal generation of contact quenched universal reporter oligonucleotides. Abstract : In this study we optimised the fluorescence signal generation of contact quenched universal reporter oligonucleotides. These are used as secondary probes in real-time Mediator Probe PCR to detect the sequence-specific cleavage of label-free primary mediator probes. Since the fluorescence signal generation of a universal reporter is not influenced by the target DNA sequence, optimisation of the fluorescence signal-to-noise ratio will improve the performance of all Mediator Probe PCRs that are based on this type of universal reporter. To determine the critical factors influencing signal-to-noise optimisation, we systematically analysed four parameters. These parameters were type of fluorophore, type of quencher molecule, intramolecular orientation of both residuals, and the number of quencher labels. In total, more than 30 different fluorogenic universal reporter structures were analysed, covering the whole fluorescence spectrum from green to crimson. From our results, we deduced a novel set of guidelines for signal-to-noise optimisation in the design of contact quenched, fluorogenic universal reporter oligonucleotides. We confirmed these guidelines in a different thermocycler, and by designing a second set of universal reporters, which were used for multiplex real-time PCR quantification of acute lymphoblastic leukaemia marker sequences. This optimised biplex Mediator Probe PCR showed an improved performance under clinical conditions, with a 10 times higher resolution regarding the limit of quantification. In addition to Mediator Probe PCR, these guidelines may also prove useful in signal-to-noise optimisation of other fluorescence-based assays where contact quenched oligonucleotides or secondary reporter molecules are used.